Inflationary impact of COVID-19 an analysis on different commodity groups in the Philippines - Cendaña, Mary Anne Clarisse R.; Cendaña, Mary Anne Clarisse R.; Alburo, Florian (Quezon City School of Economics, University of the Philippines Diliman, 2022)
The COVID-19 pandemic induced disruptions in global value chains and domestic supply chains, decreased business profits, and slowed economic growth that brought changes in demand and supply. Given supply bottlenecks and consumption shifts that differ across the different Philippine regions due to the varying severity of local cases, this paper studies the movements and differences in prices across commodity groups during the COVID-19 pandemic. Two regression models were developed using the average monthly cases of COVID-19 and inflation rates from March 2020 to December 2021 to determine the effects, namely: (1) Baseline and (2) Regional Factor Model. The results show that only 6 out of 13 commodity groups have their prices exert a significant relationship with the number of COVID-19 cases. Among the essential commodities, only food reveals a highly significant negative relationship, while among the non-essential items, only alcoholic beverages exhibit a strong negative correlation with the number of cases. Further, price movements for all items and transport are found to be negatively associated with the number of cases, while clothing and furnishings exhibit a positive relationship. Lastly, only 8.1% of the coefficients prove to have significant inflation disparities with the National Capital Region (NCR). This study recommends using one single estimator for more significant results, using other measures of inflation and exploring other pandemic indicators such as vaccination, mortality, and recovery rates.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and index.
Keywords: COVID-19 (Disease).; COVID-19 (Disease) -- Economic aspects